Customer Loyalty in the Context of Digital Marketing and Seasonal Demand: A Qualitative Study of J&C Cookies Bandung: Loyalitas Pelanggan dalam Konteks Pemasaran Digital dan Permintaan Musiman: Studi Kualitatif pada J&C Cookies Bandung - Moch. Bayu Kurniawan; Bima Wisnu Wardhana; M. Habibie Ardana Refa; Detak Prapanca (Procedia of Social Sciences and Humanities, 2026)
General Background Micro, small, and medium businesses must maintain competitiveness in a modern era where buyer retention ensures long-term operational sustainability. Specific Background J&C Cookies Bandung utilizes a multi-channel approach, combining physical outlets with social media engagement while navigating significant production surges during festive periods. Knowledge Gap Limited qualitative research explores the subjective meaning of brand allegiance when navigating the intersection of online communication and cyclical holiday purchasing behaviors. Aims This study analyzes how virtual communication, product quality perceptions, and cultural purchasing rituals collaboratively shape consumer devotion towards local pastry brands. Results The qualitative investigation reveals that enduring consumer commitment stems from a combination of consistent product quality, attractive packaging, and emotional connections tied to cultural festivities. Furthermore, integrating physical retail experiences with responsive virtual engagement creates a cohesive journey that solidifies trust and ritualistic purchasing habits. Novelty This research conceptualizes consumer devotion not merely as a rational economic decision, but as a socio-cultural phenomenon deeply rooted in cultural traditions and virtual interactions. Implications Businesses must harmonize their physical retail presence with consistent online messaging to navigate demand fluctuations and secure enduring market relevance. Highlights: Consistent product quality and attractive packaging secure long-term buyer commitment. Cultural holiday traditions transform routine purchases into meaningful emotional bonds. Harmonizing physical retail operations with virtual engagement ensures business sustainability. Keywords: Brand Trust, Consumer Experience, Multi-Channel Strategy, Holiday Traditions, Qualitative Research